Self-Assembled Redox-Active Tetraruthenium Macrocycles with Large Intracyclic Cavities - Fink, Daniel; Orth, Nicole; Ebel, Viktoria; Gogesch, Franciska S.; Staiger, Anne; Linseis, Michael; Ivanovic-Burmazovic, Ivana; Winter, Rainer F. (Organometallics, 2020)
We report on five tetranuclear metallamacrocycles with particularly large inner voids of up to 19.4 × 18.9 Å. The macrocyclic complexes were obtained by the self-assembly of spatially extended organic dicarboxylate linkers with two different dinuclear bis(alkenyl) diruthenium precursors. The five complexes include one pair of constitutional isomers, complexes 2-NB and 2-BN, which differ with respect to whether the incorporated triarylamine functionality is part of the "conductive" π-conjugated (2-NB) or the insulating dicarboxylate linkers (2-BN). All macrocyclic complexes were characterized by NMR spectroscopy, UHR ESI mass spectrometry, cyclic and square wave voltammetry, and in two instances by X-ray diffraction studies on single crystals. We also investigated the properties of their various oxidized forms via IR/NIR and UV/vis/NIR spectroelectrochemistry as well as by EPR spectroscopy. DFT studies provide further insight into the structural and electronic properties of these compounds.
CRIS-Team Scopus Importer:2020-05-22